Delayed ettringite formation in Portland cement products. - Fu, Yan. (University of Ottawa (Canada), 1996)
The thesis presents the results of an extensive research program on the deterioration of Portland cement concrete due to delayed ettringite formation (DEF). The study focuses on three aspects: (i) the mechanisms of DEF; (ii) a test method to determine the DEF potential of a given cement; (iii) some preventive measures to reduce the deterioration of portland cement products due to DEF. The research work indicates that C-S-H gel will adsorb sulfate fast at high temperature resulting in quick depletion of the gypsum phase in the portland cement-water system. Sulphate absorbed at high temperature is desorbed more slowly than that adsorbed at normal temperatures. Slower release of sulfate from an internal sulfate source may be a critical condition for DEF in high temperature cured Portland cement paste. Nucleation of a crystal requires less surface energy in a crack than in the cement paste matrix. Sulfate ions, after release from the C-S-H gel, will diffuse into the nearest microcrack and react with the Al-bearing materials in the crack to nucleate and crystallize ettringite. Growth of ettringite crystals opens the crack and damages the cement products. A test method to determine the expansion potential, due to delayed ettringite formation (DEF), of portland cements initially moist-cured at high temperatures was developed. Expansion of cement mortars made with eight different portland cements was investigated. Different test parameters, such as, curing temperature, type of sand, sand/cement ratio, specimen size and pre-treatment, were studied to select the optimal test conditions and procedures. Expansion/time criteria to evaluate the DEF potential of a given cement from the results of this test method are discussed. Siliceous materials can be used in portland cement products to reduce or eliminate deterioration due to DEF. Different siliceous materials have different characteristics relevant to the reduction of the deleterious expansion. The granulated blast-furnace slag, ggbs, and Class F fly ash are more effective in reducing the DEF expansion than Class C fly ash, silica fume and natural zeolite. The expansion of the mortar containing a siliceous material appears to be much delayed. Therefore long-term expansion should be considered in the selection of a siliceous material for use in a DEF-suspect cement. Microcracks play an important role in the expansion due to DEF. Control of microcracks using wollastonite micro-fibres should reduce the expansion of a DEF-suspect cement mortar.
Keywords: Engineering, Civil.